Fabrication and transport performance characterization of chemically-doped three-branch junction graphene device - Shaharin Fadzli Abd Rahman,; Seiya Kasai,; Abdul Manaf Hashim, (Universiti Kebangsaan Malaysia, 2013)
A graphene-based three-branch nanojunction (TBJ) device having nanowire width of 200 nm was successfully fabricated. The layer number of graphene prepared by mechanical exfoliation was determined using a simple optical contrast method which showed good agreement with theoretical value. n-type doping by Polyethylene imines (PEI) was done to control the position of Dirac point. Baking and PEI doping was found to decrease contact resistance and increase the carrier mobility. The chemically-doped TBJ graphene showed carrier mobility of 20000 cm2/Vs, which gave related mean free path of 175 nm.